Genome Sequence of Bradyrhizobium japonicum E109, One of the Most Agronomically Used Nitrogen-Fixing Rhizobacteria in Argentina - Torres, Daniela Soledad (2015)
We present here the complete genome sequence of Bradyrhizobium japonicum strain E109, one of the most used rhizobacteria for soybean inoculation in Argentina since the 1970s. The genome consists of a 9.22-Mbp single chromosome and contains several genes related to nitrogen fixation, phytohormone biosynthesis, and a rhizospheric lifestyle.